On improvement of calculations for strength of rails - E. A. Shur (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
From the middle of the last century, beginning with the works of Professor M. F. Verigo, rejection of yield strength at static loading and transition to the fatigue strength under cyclic loading were accepted and made as the main conceptual provisions in calculations of rails for strength when choosing allowable stress levels. Thus, calculation of rails for the strength should be carried out as all strength calculations of machine parts under loadings, variable in time. Further progress in the development of methods for calculating the strength of rails under varying stresses correspond with the implementation in practice of calculations of probability concepts. In article three types of calculations of rails for strength, having the greatest practical value now, are considered namely: calculation of cyclic strength of rails at prevention of formation of fatigue cracks in a foot and a neck; calculation of cyclic contact strength at prevention within a resource (or probability regulations) of formations of cracks of contact fatigue in a head of regulated shape and size, and also calculation of durability of rails taking into account existence of fatigue cracks at prevention of complete brittle fracture of all section. The main attention is paid to determination of allowable stresses when calculating cyclic strength, as well as to the accounting of a large-scale factor when calculating cyclic contact strength, and also to determination of duration of development of fatigue cracks and their critical size when calculating durability. The existing normative documents concerning calculations of rails on strength have become outdated and demand development of new ones.